Peningkatan keterampilan motorik halus melalui kegiatan menggunting pada siswa TK A - Oktriana Maya Safira; Noer Suci Endah; Muhimmatul Hasanah (Altruis: Journal of Community Services, 2022)
Early childhood education is a fundamental education, where the most important thing is the development of the child himself. In early childhood gross motor and fine motor development greatly influences the individual's activities. Fine motor development can be improved through cutting activities. This service aims to improve fine motor skills through cutting activities for kindergarten students. The subjects of this service are 3 students. This service uses the A-B-A design, which shows a stronger influence than the other designs. The results obtained from this dedication were that in the pre-test, the three subjects received an average score of 33% which can be categorized as not good, while in the post-test, the three subjects received an average score of 66% which can be categorized as sufficient. Two subjects experienced an increase during the activity, while one subject did not experience an increase even though the intervention was given. It can be concluded that in this service, there is an increase in fine motor skills through cutting activities.